Cloudy with a Chance of Conservation: How Perception Shapes Conservation Behavior - Gamble, Taylor J. (My University, 2024)
With disruptive natural events such as hurricanes, flooding, and drought-based wildfires affecting ecosystems and human communities more frequently than ever, environmental conservation is a critical issue now and going forward. In this study, I assert that individual perceptions of natural events, weather, and local climate are linked to differing attitudes and behavior related to conservation. Using the complementing interdisciplinary theories of social construction of space, construal-level theory, and social capital theory, I investigate the relationship between individual weather perception and environmental conservation behavior independent of common social, political, and ideological variables. Results from poisson regression models using data from the Oklahoma Center for Risk and Crisis Management’s 2018 national survey “Weather Society and Government” demonstrate a clear positive relationship between the perception of disruptive natural events and conservation actions. Furthermore, results show that social capital is an important moderator in this relationship. Specifically, the relationship between weather perception and conservation behavior is more pronounced for those with higher reported social capital. This study underscores the importance of environmental perceptions and social connections in predicting individual conservation behaviors.
Keywords: Conservation Behavior; Weather and Climate; Social Construction; Environmental Conservation